Monitoring and Evaluation of Late Functional Outcome in Post-treatment Follow-Up in Clinical Routine Setting - Veit Zebralla; Sylvia Meuret; Susanne Wiegand (Frontiers in Oncology, 2019)
Patients treated for head and neck cancer (HNC) often suffer from severe and visible loss of function as the cancer itself and the side effects of aggressive treatments have the potential to severely affect quality of life. Therefore, the aim of follow-up is not only the early detection of potentially curable recurrences and second primary tumors but also the diagnosis and rehabilitation of functional impairments. Clear guidelines determining the frequency of follow-up visits are missing, and the impact of follow-up visits on patient's prognosis is unclear. An intensive post-treatment follow-up is needed to detect functional impairments and to initiate their treatment. The aim is an optimal rehabilitation of the patients. This article focusses on goals of aftercare treatment and describes the spectrum of long-term sequelae, and the impact of Patient Reported Outcome (PRO) instruments of which three will be introduced.